Relationship between physical activity levels with risk of falls and social participation among elders attending daycare centers in Colombo, Sri Lanka: A descriptive cross-sectional study - Rajasinghe, U.; Dalpatadu, C. (Ceylon Journal of Medical Science, 2022)
Background: The older adult population is rapidly increasing worldwide including in Sri Lanka. Daycare centers for older adults is a newly introduced concept for Sri Lankan community-dwelling elders which has not been studied previously. Objective: To evaluate the relationship between physical activities (PA), risk of falls (RF) and social participation (SP) among community-dwelling elders from daycare centers in Colombo, Sri Lanka. Methods: Descriptive cross-sectional study. Randomly selected sixty elders (aged ≥60 years) from all six registered daycare centers in Colombo. PA, RF and SP was measured using International Physical Activity Questionnaire (IPAQ) short form, Berg Balance scale (BBS) and Participation scale (P-scale) respectively. Chi-square and Spearman correlation were used for statistical analysis. Results: AMean age (+SD) was 73.23±6.02 years. Majority were women (90%). Median (Range); BBS and P-scale scores were 51 (34-56) and 8.5 (1-52) respectively. Median (Range) PA per week was 2133 (33-6426) METminutes. A low RF was seen among 88.3% of the population, 66.7% had a high SP and 58.3% had moderate PA levels. Increased PA levels correlated with higher BBS score and lower RF (r=0.31, p<0.05). There was no significant association between PA and SP. Conclusion: High PA levels were associated with lower RF. Further studies with larger populations are recommended. Exercises programs that improve PA and balance among elders would be beneficial. Strategies that enhance social bonding and participation of elders should be promoted within the Sri Lankan society.
Keywords: community dwelling; adults; older; risk of falls; physical activity; social participation